Integration of migrants into the labour market in Europe : national, organizational and individual perspectives - Przytuła, Sylwia; Sulkowski, Lukasz, 1972- (Emerald Publishing Limited, 2020)
This volume of Advanced Series in Management offers cutting-edge research into international migration in Europe. Living and working in a host country is challenging both for the host country (for its institutions, organizations and local people) as well as for the incoming migrants. Therefore, integration activities are essential for easing the transition. The purpose of this book is to examine various practices of integrating migrants in European countries from national, organizational and individual perspectives. This publication will be valuable to researchers in the field, as well as for entrepreneurs, international corporations employing from abroad, trainers preparing employees to work in multicultural teams, as well as for investors who plan to expand their business into foreign markets.- Resumé vydavatel
Includes index.
Keywords: zahraniční pracovní síly -- Evropa; zahraniční pracovní síly -- sociální poměry -- Evropa; sociální integrace -- Evropa; foreign workers -- Europe; foreign workers -- social conditions -- Europe; social integration -- Europe; elektronické knihy; sborníky; electronic books; papers of several authors